APPLICATION OF METHOD BASED ON IN VITRO ANTIBODY QUANTIFICATION IN PBMC SUPERNATANT SAMPLES FOR IMMUNOGENICITY EVALUATION OF A (H5N1) AND A (H5N2) POTENTIALLY PANDEMIC INFLUENZA VACCINES IN CLINICAL TRIALS - I. V. Losev (Medicinskaâ Immunologiâ, 2016)
There are many data worldwide which suggest that the methods for evaluation of influenza vaccines immunogenicity should be improved. The only method validated in Russia is a HAI (haemagglutination inhibition) assay with serum samples from vaccinated volunteers. This assay does not, however, completely reflect the vaccine-induced immunological changes. In this study, we evaluated antibody immune responses to A (H5N1) inactivated influenza vaccine boosting in healthy volunteers previously primed with A (H5N2) live attenuated influenza vaccine. We compared three methods of antibody detection: (i) HAI assay with serum samples; (ii) ELISA with serum samples; (iii) ELISA with PBMC (peripheral blood mononuclear cells) culture supernates, i.e., an alternative test based on quantification of antibodies secreted by PBMC in vitro. The latter test was shown to have an advantage over other techniques in IgA and IgG antibody detection at early timepoints (day 7) after vaccination. The first two methods allowed immunogenicity assessment at day 28 after vaccination.Thus, a test based on antibody quantification in PBMC supernatant samples can be used as an alternative method for evaluation of influenza vaccines immunogenicity. This method also exhibits a better strainspecificity.